A 2 × 2 Filtering subarray element antennas using all‐resonator structures. Issue 6 (22nd March 2021) - Mahmud, Rashad H.; Lancaster, Michael J.
Abstract: This study presents two novel topologies of a 2 × 2 filtering antenna subarray based on all resonator structures. The coupling matrix theory is used to extract the interresonator coupling coefficients and quality factors. The matrix parameters give a controllable bandwidth to the filtering subarrays. Rectangular waveguide cavity resonators are utilised to implement the physical layouts of the topologies. They operate at a centre frequency of 10 GHz and have a fractional bandwidth of 10% with return loss of ‐20 dB. The first topology consists of seven resonators feeding from beneath, while the second topology consists of six resonators feeding from the side. Compared to previous 2 × 2 waveguide cavity‐backed subarray antennas, the proposed 2 × 2 filtering subarrays have the advantage of having a larger bandwidth, flatter gain over the passband and larger roll‐off of the gain at the band edges. Also, when providing the feed network, the all‐resonator structure removes the need to place a bandpass filter after the antenna at the front end of a communication system. Fabrication and measurements have been performed by validating the designs.